Puccinia xanthii Penyebab Bercak Daun pada Xanthium sp. di Indonesia - Dono Wahyuno (Jurnal Fitopatologi Indonesia, 2012)
An obligate plant parasitic rust fungi found on leaf of Xanthium sp. that grows wildly in Raihat County, Belu District of East Nusa Tenggara Province. Morphological observation of the fungal structure under compound light microscope revealed the fungus belongs to Puccinia. Spore is pedicelate, the pedicles were hyaline, 10,0-(20,9)-30.0 μm long and 3.8-(4.9)-7.5 μm wide; the teliospores were orange to light brown color, 22.5-43.9)-55.0 μm long, and 15.0-(17.3) 20.0 μm wide; the apical thickening wall present at the spore tip, 3.8-(6.6)-10.0 μm thick and has microcyclic life cycle type. The fungus was identified as Puccinia xanthii and this is the first report the occurrence of the fungus in Indonesia.Key words: leaf spot, Puccinia xanthii, Xanthium